Reconsideration of Significant Quantity (SQ) for Pu Based on the Strategic Impact Investigation of Non-Strategic Nuclear Weapon (NSNW) Using Monte-Carlo Simulations - Woo, Seung Min; Lee, Manseok; Ryu, Je Ir (Journal of nuclear fuel cycle and waste technology (Online), 2021)
The present multidisciplinary study, which is a nexus of engineering and political science, investigates how the modernization of Non-Strategic Nuclear Weapons (NSNWs) affects the IAEA safeguards system based on the likelihood of the use of nuclear weapons. To this end, this study examines the characteristics of modernized NSNWs using Monte Carlo techniques. The results thus obtained show that 10 kt NSNWs with a Circular Error Probability (CEP) of 10 m can destroy the target as effectively as a 500 kt weapon with a CEP of 100 m. The IAEA safeguards system shows that the Significant Quantity (SQ) of 1 of plutonium is 8 kg, a parameter that was established when strategic nuclear weapons were dominant. However, the results of this study indicate that in recent years, low-yield nuclear weapons such as NSNWs have been more strategically interesting than strategic nuclear weapons as NSNWs require less plutonium than strategic nuclear weapons. Therefore, we would like to conclude that reducing the SQ of plutonium can result in more robust safeguards and non-proliferation strategies.